Design an automatic trash can using the HC-SR04 ultrasonic sensor based on the Arduino Uno microcontroller - Anggi Kumala Dwi; Mulkan Iskandar Nasution; Nazaruddin Nasution (Universitas Riau, 2024)
Garbage is one of the biggest problems faced by many cities in the world, the lack of awareness to dispose of waste in its place causes waste to scatter and pollute the surrounding environment. This research aims to design an automatic trash bin based on the Arduino microcontroller and to find out how the automatic trash can works with the HC-SR04 ultrasonic sensor based on the Arduino Uno microcontroller. The design of this system uses Arduino Uno. The results of the input and output tests show that the HC-SR04 ultrasonic sensor has a low error rate of 1.2% at a distance of 25 cm and a high of 6% at a distance of 10 cm. The trash can opens the lid automatically at > 30 cm to detect the capacity of waste that has been disposed of into the trash container with a height of 20 cm., the proximity sensor will detect the type of waste being disposed of, and the LCD will display the type of waste that will be disposed of and the servo motor will activate the mechanical system of this device. If the trash can is full, a warning will be sent via the buzzer and the SIM800L GSM module via SMS. The working system of the automatic trash can as a whole can work well according to the design that has been made.